PELATIHAN DAN PENDAMPINGAN DIGITALISASI ADMINISTRASI PENJUALAN PADA KELOMPOK WANITA TANI " DEWI SARTIKA" DESA PETUNG SEWU KABUPATEN MALANG - Evi Suwarni; Vit Zuraida; Tiara Estu Amanda; Widi Dwi Ernawati; Masitha Nisa Akmalia (Jurnal Pengabdian kepada Masyarakat, 2024)
This Community Service aims to provide assistance and training for the Petung Sewu Village Farmer Women's Group, Malang Regency, namely the Petung Sewu Village farmer women's association that processes citrus drinks which currently does not have proper business administration records, resulting in irregular recording and proof documents, inseparability between personal money and business capital and business results, In fact, often it cannot be known the profit and loss from the proceeds of sales. This community service activity is in the form of assistance to the Petung Sewu Village Farmer Women's Group, Malang Regency in terms of managing business administration activities systematically using the TemanBisnis application to facilitate the management of administrative activities so that all administrative activities can be recorded properly. The method used is to hold assistance and training on the use of digital financial administration records, namely the "Business Friends" application. The end result of this activity is the application of a good digital sales administration system to realize an orderly administrative business and ease of financial records, financial statements. Real time information in this system helps the business operations of the Farmer Women's Group of Petung Sewu Village, Malang Regency more effectively and efficiently. Keywords: Farmer Women's Group, Digital Sales Administration, TemanBisnis